The impact of rumen microbial composition on apparent digestibility, rumen fermentation and metabolism in Sanhe cows and Holstein cows of different parities under identical dietary conditions - Liu, Zixin; Jiang, Aoyu; Ma, Dianyu; Liu, Dexin; Han, Xiaoyu; Zhao, Man; Zhou, Chuanshe; Tan, Zhiliang (Frontiers in Veterinary Science, 2025)
Previous studies have discussed the association between serum metabolism and lactation performance among Sanhe and Holstein cows of different parities and found that the metabolic profiles of these two breeds vary differently with parity. Since the rumen is the central organ for nutrient absorption and production transformation in dairy cows, it remains unknown whether the differences observed under the same dietary conditions are related to the structure of the rumen microbiome. This study measured the apparent digestibility and rumen fermentation parameters of Sanhe cows (S1/S2/S3/S4) and Holstein cows (H1/H2/H3/H4) across four parities and generated a comprehensive rumen microbiome dataset using high-throughput sequencing technology. Significant differences in dry matter digestibility (p = 0.001) and ammonia nitrogen (p = 0.024) were observed among the S groups, with higher trends of various VFA contents in S1 (0.05 < p < 0.1). The H group showed significant differences in crude protein digestibility (p = 0.001), higher isovaleric acid content in H1 (p = 0.002), and the lowest acetate to propionate ratio (p = 0.002) in H3. Metagenomic sequencing results indicated consistency between rumen microbiome patterns and metabolic changes, with S1 distinctly different from S2/S3/S4, and H1 and H2 different from H3 and H4. The species composition of the rumen microbiome was similar between Sanhe and Holstein cows, but differences in abundance were noted. Rhizophagus <glomeromycetes>, Neocallimastix, and Piromyces were more abundant in S1, H1, and H2, and pathways such as autophagy-animal, plant-pathogen interaction, and endocytosis were significantly enriched in these parities. Multiparous Sanhe cows had higher abundances of ATP-binding cassette transporters pathways. Additionally, CAZymes such as GH84 and GH37 were significantly associated with differential physiological indicators and milk traits. In conclusion, this study reveals the complex relationship between rumen microbiota and metabolic characteristics in Sanhe and Holstein cows of different parities, indicating that changes in the structure of the rumen microbiome may be key factors affecting lactation performance and metabolic differences in dairy cows.